The Role of English Fiction in North Borneo: An Analysis of Short Stories in English News Dailies from 1949 to 1963 - Alvin Azril Mahat; Sim, Chee Cheang (Penerbit Universiti Malaysia Sabah, 2023)
The focus of this paper is the role of English news dailies published from 1949-1963 in North Borneo during the British North Borneo Company (BNBC) administration which began its operations in Sandakan from 1881 to 1941. This paper aims to uncover the cultural expression, social commentary, and political discourse, offering a glimpse into the concerns, and aspirations of the local community through an analysis of short stories published in two particular English News dailies which is 'Anak Sabah' and 'North Borneo News,' A mixed-methods approach that utilizes Stephen Greenblatt’s (2000),(2005) New Historicism and archival analysis, textual analysis, and content analysis is employed to achieve the objectives of this research. Because historicism, history, and literature are intertwined (Bakar et al., 2022) it is and short stories have a rich and enduring history, akin to a perennial river that flows with renewed vigour and an ever-expanding array of variations (Thambi Jose, 2019), the findings will unravel the connections between the fiction in the non-fiction world that influenced the social cultural contexts that shaped the literary heritage of Sabah.